The Burnout Dyad: A Collaborative Approach for Including Patients in a Model of Provider Burnout. Issue 4 (1st October 2021) - Martinez-Hollingsworth, Adrienne; Hicks, Melissa; Dobrota, Sylvie; Chu, Larry F.
Abstract: Both patients and providers in the United States (US) suffer from burnout, which can impact the clinical relationship and quality of care. Among providers, burnout is a state of exhaustion including heightened depersonalization; among patients, burnout can negatively affect clinical outcomes. More than half of clinical providers in the United States suffer from burnout; less is known about the magnitude and prevalence among patients. Understanding patient burnout will improve our recognition of treatment barriers, understanding of patient-provider communication, and perceived quality of care. The purpose of the 2019 Stanford University MedicineX Burnout Workgroup was to use a collaborative approach to expand on the National Academy of Medicine (NAM) Wellness and Resilience Model, which does not currently include the patient as an influential member of the care team potentially experiencing burnout. This collaboration among patients, physicians, students, caregivers, technologists, and researchers used a convenience sample of conference attendees, broken into three focus groups to (1) provide an expanded definition of burnout that includes patients' perspectives, (2) analyze the NAM burnout model for inclusion of the patient experience, and (3) define a care experience that includes both patients and providers. The design of this workgroup was informed by Everyone Included, a model that recognizes and rejects hierarchical traditions in clinical practice. This approach allowed for the creation of a safe space for the exchange of knowledge between the various stakeholders. The resulting inclusive conceptual model, The Burnout Dyad, describes a cocreated care experience informed by both patient and provider characteristics.